Unraveling water relations in growing fruit: insights from the epidermal growth regulation hypothesis - Gariglio, Norberto; Reig, Carmina; Agustí, Manuel (Frontiers in Plant Science, 2024)
This review focuses on the intricate water relationships between internal and external tissues in growing fruits within the framework of the epidermal growth control hypothesis. It considers the components of water potential, including turgor pressure and osmotic potential of both internal and external tissues, taking into account factors such as fruit growth rate, sugar accumulation, cell wall metabolism, and climacteric. It also examines the effects of environmental conditions, genetic factors and physiological influences in modifying water relations. By emphasizing the significance of skin tissue water potential components as indicators of growth stress, the review underlines their importance for a comprehensive understanding of water relations and associated physiological disorders in growing fruit.